Periodontal Treatment Needs of Patients with Chronic Kindey Disease - Zainab Amjad Haroon, Fatimah Imran, Asma Shakoor, Nida Ayub4, Ahmed, Nawal Noor, Hira Butt (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the periodontal treatment needs of patients in different stages of chronic kidney disease Methodology: A Cross sectional comparative study was conducted in the department of Nephrology and Urology, Sharif Medical and Dental College, Lahore on 32 patients with chronic kidney disease in the time duration of one year. Data was collected after taking an informed consent from the patients. The demographic data along with a list of variables associated with chronic kidney disease was recorded using a structured questionnaire. Data collection was based on the following parameters: Community Periodontal Index of Treatment Needs (CPITN). Results: The highest percentage (10%) of patients who required no treatment (TN0) were stage 3 patients. Majority of the stage 5 (93.1%) patients required scaling, prophylaxis and oral hygiene instruction (TN2) followed by stage 4 (90.9%) and stage 3 (40%) respectively. None of the patients required complex treatment, scaling, prophylaxis and oral hygiene instructions (TN3) Conclusion: The highest percentage of patients with healthy periodontium were stage 3 patients. Periodontal pocket depths 4-5 mm were found to be in stage 4 patients the most followed by stage 5 and then stage 3. None of the patients had pocket depths of 6mm or more. Majority of the stage 5 patients required scaling, prophylaxis and oral hygiene instruction (TN2) followed by stage 4 and stage 3 respectively. None of the patients required complex treatment, scaling, prophylaxis and oral hygiene instructions (TN3). Keywords: Chronic kidney disease, periodontal treatment needs, oral hygiene instructions, oral prophylaxis, complex treatment